2018
DOI: 10.20546/ijcmas.2018.706.187
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability, Heritability and Genetic Gain in Advanced Mutant Breeding Lines of Sesame (Sesamum indicum L.)

Abstract: In present investigation, 133genotypes comprised of advanced mutant breeding lines, germplasm lines, genotypes pertaining to Initial Varietal Trial, Advanced varietal Trial and Multi Location Trial, popular varieties national, zonal and local checks were evaluated for assessment of genetic variability at Regional Agricultural Research Station, Jagtial with Randomized Block design in 3 replications. Influence on breeding programmes is especially based on the extent to which variability occurs and the relative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Conversely, Divya et al. (2018) and Aye and Htwe (2019) reported high heritability and high genetic advance for plant height and number of capsules per plant in Indian and Myanmar sesame germplasm collections. Traits with high heritability and high genetic advance are reported to be under the control of additive gene action.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, Divya et al. (2018) and Aye and Htwe (2019) reported high heritability and high genetic advance for plant height and number of capsules per plant in Indian and Myanmar sesame germplasm collections. Traits with high heritability and high genetic advance are reported to be under the control of additive gene action.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, higher heritability and genetic advance were computed for the number of secondary branches. Conversely, Divya et al (2018) and Aye and Htwe (2019) Association analysis of economic traits is vital to improve selection efficiency for breeding. In the present study, genetic correlation analysis revealed positive and highly significant associations between seed yield per hectare with thousand seed weight, and oil yield per hectare number of seeds per capsule and number of capsule per plant with oil yield (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations